2017
DOI: 10.1080/01443410.2016.1271402
|View full text |Cite
|
Sign up to set email alerts
|

Dominant achievement goals and academic outcomes across tracks in high school

Abstract: The self-reported grades Dutch, English and Math of 13,970 students in the third grade of Dutch secondary education (US grade 9) were investigated with regard to educational track-level and dominant achievement goal (DAG). The performance approach goal group scored significantly higher on all three subjects than the performance avoidance group, the mastery approach group, the mastery avoidance group and the group without a DAG. In addition, the differences between the performance approach group and the other g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 44 publications
(77 reference statements)
6
9
0
Order By: Relevance
“…The above suggests that the dominant achievement goal (DAG) is eminently suited for longitudinal studies. In the last decade a couple of studies showed that most people have a DAG (de Lange et al, 2010;Fernandez-Rio et al, 2014;Scheltinga et al, 2016;Scheltinga, Timmermans, & van der Werf, 2017;Van Yperen, 2006;Van Yperen et al, 2011;Van Yperen & Orehek, 2013;Van Yperen & Renkema, 2008). In domains such as education, the workplace or sports, people tend to prefer one specific achievement goal over the other goals from the 2x2 achievement goal framework (Elliot & McGregor, 2001).…”
Section: The Dominant Achievement Goalmentioning
confidence: 99%
See 4 more Smart Citations
“…The above suggests that the dominant achievement goal (DAG) is eminently suited for longitudinal studies. In the last decade a couple of studies showed that most people have a DAG (de Lange et al, 2010;Fernandez-Rio et al, 2014;Scheltinga et al, 2016;Scheltinga, Timmermans, & van der Werf, 2017;Van Yperen, 2006;Van Yperen et al, 2011;Van Yperen & Orehek, 2013;Van Yperen & Renkema, 2008). In domains such as education, the workplace or sports, people tend to prefer one specific achievement goal over the other goals from the 2x2 achievement goal framework (Elliot & McGregor, 2001).…”
Section: The Dominant Achievement Goalmentioning
confidence: 99%
“…Results regarding the association of the DAG with performance outcome measures, however, are reported only by Scheltinga et al (2017) and Van Yperen (2006). In the latter study, Van Yperen ( 2006) used the average score on final course grades of 109 sophomore and 170 junior students enrolled as majors in the science department at a university in the Netherlands to examine the various DAG groups.…”
Section: The Dominant Achievement Goalmentioning
confidence: 99%
See 3 more Smart Citations